Maternal depression and its correlates – a longitudinal study - Nabia Tariq; Humera Naeem; Ayesha Tariq; Sajida Naseem (Journal of the Pakistan Medical Association, 2021)
Objective: To estimate the burden of Antenatal Depression (AND) and Postpartum Depression (PPD) and explore possible predictors of Perinatal Depression (PND). Methods: A longitudinal study was conducted in the department of obstetrics and gynecology in Shifa International hospital and its community health care center in Islamabad, Pakistan from October 2018 to May 2019 after taking Ethical approval of institutional review board and ethical committee. It included 200 women in their third trimester of pregnancy. Women not consenting, chronic or critically ill, having psychological disorders, medical co morbid or on medications were excluded. Socioeconomic and obstetrical history was recorded on a separate Performa and Edinburgh Postnatal Depression Scale was used for screening of depression in these women. SPSS was used for data analysis. Linear regression analysis was done to see the association between antenatal and postpartum depression scores. Results: Women in postnatal period had higher Depression scores than women in antenatal period. 12.5% women had AND whereas 36.5% had PPD. Results also suggest that AND increases the risk of PPD. The results also imply that PPD scores are higher in women having unplanned pregnancies and multigravida. Moreover, women belonging to middle and lower class were more prone to PND. Conclusion: It was concluded that AND was strongly associated with PPD indicating AND to be a significant predictor of PPD. Social class and parity are directly linked with prevalence of PND. Continuous...